Learning through network interaction: The potential of ego-networks - Ünlüsoy, Asli; de Haan, Mariette; Leander, Kevin (Proceedings of the International Conference on Networked Learning, 2012)
This study deals with online personal social networks (i.e., ego-networks) of youth 12-18 years old, in the Netherlands and investigates if and how these networks operate with respect to learning. The online ego-networks of youth, and the potential these networks have for learning, are largely unexplored. What kinds of resources do youth have access to through their networks? With whom do they connect? How can we characterize these relations in terms of the frequency they meet online and offline, emotional closeness, topics of conversation, and geographical dispersion of contacts? What kinds of networks provide learning experiences? How can we predict these networks? This study describes in detail the characteristics of these ego-networks. Furthermore, we tested the claim that learning in online networks is a likely result of frequent network activity. Particularly we questioned if popular social network activities such as sharing links, giving feedback and editing or creating artefacts together online would be related to the discovery of new information. With a multi-level analysis model we were able to differentiate the individual influences and the influence of their ego-networks on the frequency of discovering new information and overall network activity. The results showed that these network activities strongly and positively predicted discovery of new information. With respect to the people with whom youth construct their networked communities, the study show that youth connects online primarily with contacts who are similar, who live close by and who are emotionally close. In contrast to claims in the literature in which innovation and learning is associated with heterogeneous contacts, these results show that youth chooses homogeneous, emotionally close and locally based online relationships to explore their interests, to relate to and to discover new information together. A possible explanation may be that in this age group, youth are still fostering the ties to their immediate community and that being accepted and being similar may allow for a safer exploring of the world. These results suggests that rather than stating how a particular kind of tie or network predicts innovation, or is likely to provide new information, these relations need to be contextualised and understood from their local, specific settings and social dynamics.